2006
DOI: 10.5194/angeo-24-1455-2006
|View full text |Cite
|
Sign up to set email alerts
|

ULF fluctuations of the geomagnetic field and ionospheric sounding measurements at low latitudes during the first CAWSES campaign

Abstract: Abstract.We present an analysis of ULF geomagnetic field fluctuations at low latitudes during the first CAWSES campaign (29 March-3 April 2004). During the whole campaign, mainly in the prenoon sector, a moderate Pc3-4 pulsation activity is observed, clearly related to interplanetary upstream waves. On 3 April, in correspondence to the Earth's arrival of a coronal mass ejection, two SIs are observed whose waveforms are indicative of a contribution of the high-latitude ionospheric currents to the low-latitude g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
2
15
1
Order By: Relevance
“…Additionally, the electron density of the ionosphere increased and then gradually recovered to the original level, which is a typical case of plasmasphere depletion in response to the solar wind dynamic pressure pulsation during a geomagnetically quiet period. This result is consistent with the findings that the plasmaspheric density decreased at mid-and low-latitude during the magnetic storm proposed by Chi et al [2] and Villante et al [15] and our previous result that showed a corresponding decrease of the plasmaspheric density during moderate magnetic storm events in 2011.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…Additionally, the electron density of the ionosphere increased and then gradually recovered to the original level, which is a typical case of plasmasphere depletion in response to the solar wind dynamic pressure pulsation during a geomagnetically quiet period. This result is consistent with the findings that the plasmaspheric density decreased at mid-and low-latitude during the magnetic storm proposed by Chi et al [2] and Villante et al [15] and our previous result that showed a corresponding decrease of the plasmaspheric density during moderate magnetic storm events in 2011.…”
Section: Summary and Discussionsupporting
confidence: 93%
“…On the other hand, as noted earlier, the correspondence between spectral enhancements in the magnetospheric field and SW density led Kepko et al [2002] and Kepko and Spence [2003] to interpret the discrete frequencies in terms of an inherent property of the SW, not related to cavity or waveguide modes of the magnetosphere. Recently, Villante et al [2006] presented a case in which power enhancements ( f ≈ 1.4, 2.5, and 4.2 mHz) simultaneously occurred in the H component as well as in the radial component of the SW speed and IMF, while the SW density showed minor enhancements at different frequencies; they speculated, in that case, noncompressive “Alfvénic” fluctuations as possible drivers of geomagnetic field fluctuations at discrete frequencies.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Though it is needed to further examine conditions to relate IMF fluctuations to magnetospheric variations, it is suggested that IMF Alfvénic fluctuations is an important source for the excitation of magnetospheric waves. Villante et al (2006) also speculated that Alfvénic fluctuations as possible drivers of geomagnetic field fluctuations at discrete frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…As for IMF changes, multiple spectral peaks at 1.7, 2.1, 2.7 and 3.7 mHz were noted, which roughly correspond to those of magnetospheric oscillations. Villante et al (2006) have presented a case in which power enhancements (at 1.4, 2.5, and 4.2 mHz) simultaneously occurred in the H component on the low latitude ground as well as in the radial component of the SW speed and IMF, while the SW density showed minor enhancements at different frequencies. This observation is essentially similar to the case discussed above.…”
Section: August 20 1999mentioning
confidence: 99%